Integration in the European Research Area by means of the European Framework Programmes. Findings from Eigenvector filtered spatial interaction models - Thomas Scherngell; Rafael Lata (European Regional Science Association (ERSA), 2011)
One of the main goals of the European Research Area (ERA) concept is to improve coherence and integration across the European research landscape by removing barriers for collaborative knowledge production in a European system of innovation. The cornerstone of policy instruments in this context is the European Framework Programme (FP) that supports pre-competitive collaborative R&D projects, creating a pan-European network of actors performing joint R&D. However, we know only little about the contribution of the FPs to the realisation of ERA. The objective of this study is to monitor progress towards ERA by identifying the evolution of separation effects, such as spatial, institutional, cultural or technological barriers, which influence cross-region R&D collaboration intensities between 255 European NUTS-2 regions in the FPs over the time period 1999-2006. By this, the study builds on recent work by Scherngell and Barber (2009) that addresses this question from a static perspective. We employ Poisson spatial interaction models taking into account spatial autocorrelation among residual flows by using Eigenvector spatial filtering methods. The results show that geographical distance and country border effects gradually decrease over time when correcting for spatial autocorrelation among flows. Thus, the study provides evidence for the contribution of the FPs to the realisation of ERA.
Keywords: 330